VARIABEL YANG MEMPENGARUHI STRUKTUR MODAL DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (STUDI PADA INDUSTRI MANUFAKTUR DI BURSA EFEK INDONESIA) - Diana Dwi Astuti; Chusnul Hotima (UPT Penerbitan Universitas Jember)
This study aimed to analyze the influence asset structure, company size, growth, liquidity business risk to capital structure with profitability as an intervening variable in companies listed on the Stock Exchange in 2010-2014. The data used in this research is secondary data. Selection of the samples in this study conducted by purposive sampling. Based on the existing criteria, obtained a sample of 17 companies. Data analysis technique used is path analysis. Based on the analysis of data from five independent variables only variable asset structure and liquidity influential significance to profitability, while the variable size of companies, growth companies, and business risk has no significant effect on profitability. And of the six independent variables only variables that affect the liquidity of the capital structure. In the independent variables are able to moderate profitability variable asset structure, growth, liquidity and business risks, while veriabel sized companies can not afford to moderate profitability on capital structure.